Association Between COVID-19 Infection and New-Onset Diabetes in a Tertiary Care Hospital in Kathmandu - Adhikari, Prabin; Devkota, Krishna Chandra (Nepal Medical College Journal, 2023)
In severe acute respiratory syndrome coronavirus 2 infections, reduced numbers of insulin secretory granules in beta cells and impaired glucose-stimulated insulin secretion have been observed, with insulin resistance and the onset of diabetes in them. This study was conducted to find the association between COVID-19 infection and new-onset diabetes. This was a cross-sectional study conducted in the Department of Internal Medicine at Nepal Medical College Teaching Hospital, for a duration of 6 months (July to December 2021). A total of 38 new-onset diabetes patients with a confirmed history of COVID-19 infection were enrolled in the study using a non-probability convenient sampling technique. Ethical clearance was taken from the Research and Institutional Review Committee, Nepal Medical College Teaching Hospital (Reference No.068- 077/078). Venous blood was collected and fasting blood glucose, post-prandial blood glucose, and HbA1c were measured. Data were analyzed in the Statistical Package for Social version 20.0. Analytical data were compared using Z- test for the parametric values and the Chi-Square test for the nonparametric values. Statistical significance was defined as a p-value of less than 0.05. As per clinical severity, 22 had mild, 13 had moderate and three had severe COVID-19 infection. The mean fasting blood sugar was 169.84 ± 40.72 mg/dl and the mean postprandial blood sugar was 249.92 ± 72.46 mg/dl. The mean HbA1c was 7.92 ± 1.11%. Out of 38 patients, 36 had a history of systemic steroid use and hyperglycemia was significantly associated with steroid use (Z=1.97, P=0.024).